Bioethical Justification of Private Umbilicoal Cord Blood Banking - Losada Pescador, Agustín (Studia Bioethica, 2012)
Umbilical cord blood stem cells are a good therapeutic option in haematological malignancies such as leukemia or lymphoma. Their usefulness is undisputed when used for transplants in matched siblings, resulting in many cases the best alternative. Moreover, their usefulness in autologous transplants is becoming increasingly evident. In addition to current applications, there are several studies on going that could enable their use in cell therapy and regenerative medicine. Thus, family banking makes all sense, by provinding parents the possibility to offer all health options to their children for the future. The objections to their development are based on prejudices and collectivists assumptions, since there are no scientific or ethical reasons to condemn them.